2005
DOI: 10.1016/j.neures.2004.12.019
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic neurons in inferior colliculus of the GAD67-GFP knock-in mouse: Electrophysiological and morphological properties

Abstract: Utilizing slice preparations of GAD67-GFP knock-in mouse, in which GABAergic neurons are specifically labeled with GFP fluorescence, we studied electrophysiological characteristics of GABAergic neurons of IC by whole-cell patch clamp-recording combined with biocytin-intracellular-staining techniques. GABAergic neurons of IC fell into two distinct firing types; (1) tonic type neurons and (2) transient (phasic) type neurons. Tonic type neurons showed regularly repetitive discharge pattern in response to a long d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 59 publications
12
80
0
Order By: Relevance
“…C57BL/6 mice (3,7,14,21, and 60 d old; Charles River) and GAD67-green fluorescent protein (GFP) (Ono et al, 2005) and glial fibrillary acidic protein (GFAP)-GFP (The Jackson Laboratory) transgenic mice were used. Animals of either sex were used for 3-to 21-d-old mice, and only males were used for the adult animals.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice (3,7,14,21, and 60 d old; Charles River) and GAD67-green fluorescent protein (GFP) (Ono et al, 2005) and glial fibrillary acidic protein (GFAP)-GFP (The Jackson Laboratory) transgenic mice were used. Animals of either sex were used for 3-to 21-d-old mice, and only males were used for the adult animals.…”
Section: Methodsmentioning
confidence: 99%
“…We used a transgenic mouse expressing EGFP under the control of the endogenous promoter for GAD67, a synthetic enzyme for GABA. In contrast to the commercially available "GIN" mouse, which only expresses GFP in a particular subset of rNST GABAergic neurons (Travers et al 2007;Wang and Bradley 2010a), this GAD67-GFP knockin strain has been shown to produce EGFP in virtually all cells expressing GAD67 (Brown et al 2008;Kaneko et al 2008;Ono et al 2005;Tamamaki et al 2003), allowing for a more complete identification of GABAergic neurons in the NTS. Because of reports that monosynaptic inputs to GABAergic neurons in the rNST may diminish during development in rat (Wang et al 2012) but evidence for presynaptic inhibition of monosynaptic vagal inputs to cNST GABAergic neurons in mature as well as young mice (Glatzer et al 2007), we included both mouse pups (P14 -18) and adult mice (6 -11 wk) in our study.…”
Section: Methodsmentioning
confidence: 99%
“…First, the different transgenic mouse strains we used to identify GADexpressing neurons appear to reliably label GABAergic neurons (Tamamaki et al, 2003;Lopez-Bendito et al, 2004;Marowsky et al, 2005;Zhang et al, 2006) but may not label all GAD neurons in every CNS region. Nevertheless, the GAD67-GFP mouse line was created using homologous recombination, and as such, all neurons that express GAD67 would be expected to drive the expression of GFP (Tamamaki et al, 2003), and this situation has been described in several CNS regions (Ono et al, 2005) including the brainstem [Li et al (2005), their Fig. 2].…”
Section: The Inm Contains Neurochemically Diverse Neuronsmentioning
confidence: 99%